EFL Students’ Preferences Towards Written Corrective Feedback: An Exploratory Study on Age and Level of Proficiency - Orts, Sara; Salazar, Patricia (The Grove - Working Papers on English Studies, 2016)
Corrective feedback (CF, henceforth) has been an issue of investigation in second language acquisition for a number of years now. In the English-as-a-foreign-language classroom, students may have different preferences towards how to have their errors corrected. Research has shown that differences in the learning styles of the students will affect the learning environment by either supporting or inhibiting their intentional cognition and active engagement. In the classroom, teachers can use this information as a tool to motivate students and help them improve in their learning process. This exploratory study was carried out to analyse students’ preferences towards written correction in two different groups at a high school in Spain. Students filled out a questionnaire and results were analysed in order to determine whether age and level of English may be factors affecting their preferences for error correction.